Pathé et l'institutionnalisation du cinéma (Cinéma & Cie. Film and Media Studies Journal, 2013)
While it is possible to define one aspect of cinema's institutionalisation during the first twenty years of French film as the process of normalising quality in a more or less consensual and lasting manner, this article seeks to show, through the case of Pathé and its role in this institutionalisation, that the quality at issue was cinematic and not simply filmic. Employing a vast collection of sources taken from the press of the day, this study offers a typology of different forms of quality in cinema as they were seen at the time of this initial phase in the institutionalisation process.